The Importance of Rural, Township, and Urban Life in the Interaction between Social and Emotional Learning and Social Behaviors - Totan, Tarik; Ozyesil, Zumra; Deniz, M. Engin; Kiyar, Fatma (EDAM, 2014)
Whether an individual lives in a rural or urban setting may have direct impact on a wide variety of psychological patterns adopted by students. In this study, the effects of positive and negative social behaviors on the relationship between social and emotional learning needs and skills gaps of students who reside in both rural and urban areas have been examined. The participants of this research consist of 348 female and 319 male students, forming a total of 667 middle school students living in the province of Canakkale, Turkey as well as in its surrounding areas. The Matson Social Skills Evaluation Scale, the Social-emotional Learning Scale, the Social and Emotional Learning Skills Scale, and personal information form were used to collect data for this research. The Baron and Kenny's approach and the Sobel test were followed during the examination of the model created in the data analysis process. The mediator test examined the effects of positive and negative social behaviors in relationship to students' level of social and emotional learning needs and social and emotional learning skills. As a result of this test, it was found that both positive and negative social behaviors exert partial mediation effects over students living in rural and urban areas of the province of Turkey researched.
Keywords: Rural Life; Social and Emotional Learning; Social Skills; Urban Life; SKILLS; CHILDREN; PROGRAM; NEEDS; Education & Educational Research